Growth analysis of pods and seeds of seven genotypes of Theobroma Cacao L. - Almeida, Alex-Alan F. de; Valle, Raúl René (Pesquisa Agropecuaria Brasileira, 1995)
Pod and seed growth of cacao (Theobroma cacao L.) clones SIAL-169, SIAL-505, SIC-23, SIC-328, ICS-1, ICS-8 and the cultivar Catongo were studied under field conditions at the Cacao Research Center - CEPEC -, Ilhéus, Bahia, Brazil, to determine variations in the rates of dry matter accumulation. Ten to 15 adult trees of these genotypes were hand pollinated to mantain a pod set of 20 pods per tree. During pod ontogenesis, 14 samplings were taken at regular intervals in the 202 days of the experiment. The sampling began 35 days after pollination. At the end of the experimental period, ICS-8 and ICS- 1 showed the highest values of total dry matter accumulation and rates of pod growth. The clones SIC-23 and SIC-328 had the lowest values. There were variations in width and hight of the curves of total dry matter accumulation rates of pods and seeds of the different genotypes. The maximum hight and width were found in ICS-8 and in ICS-1 and were lowest in SIC-328. The highest increment in pod and seed dry matter of those genotypes was attributed to their higher accumulation rates and greater filling periods.